The Hygiene Hypothesis – Learning From but Not Living in the Past - Pfefferle, Petra I.; Keber, Corinna U.; Cohen, Robert M.; Garn, Holger (Frontiers in Immunology, 2021)
Since postulated by David P Strachan more than 30 years ago, the Hygiene Hypothesis has undergone many revisions and adaptations in its 30 years. This review takes a journey back to the beginnings of the Hygiene Hypothesis and describes the most important of the many aspects that have refined and generalized the Hygiene Hypothesis over time. Starting from an epidemiological approach, the Hygiene Hypothesis advanced to a comprehensive concept which nowadays is far beyond the initial attempt to just explain the development of allergies. Within the last 30 years the Hygiene Hypothesis covered immunological, microbiological and evolutionary evidence. Thus the original postulate developed into a holistic model that explains discrepancies between the human being equipped by the evolution for a life close to nature and the post-modern life-style which has drifted far from it. Focusing on diet and the microbiome as a most prominent exogenous stimuli we exemplarily describe these discrepancies and the resulting health outcomes and point out to future solutions to reestablish the immunological homeostasis that got lost in westernized societies.